Challenges and Opportunities for Islamic Religious Education in a Secular Environment in a Literature Review - Rifky, Sehan; Nasution, Muhammad Ali Azmi; Selvia, Devi Sela Eka; Isti'ana, Ais; Yusnita, Erni (Permata : Jurnal Pendidikan Agama Islam, 2024)
Islamic religious education faces various challenges that develop along with the times and social changes. Globalization, technology, politicization of religion, multiculturalism, and exclusivism are some of the main factors influencing the dynamics of Islamic religious education today. This research aims to discover the challenges and opportunities of Islamic religious education in a secular environment. The methodology used in this research is a literature study. The research results show that Islamic religious education in a secular environment faces complex challenges such as globalization, technology, multiculturalism, and religious exclusivism. Globalization brings secular values that conflict with Islamic religious teachings, while multiculturalism demands interfaith tolerance. Changes in the educational paradigm also require Islamic religious education to adapt to more holistic learning. However, opportunities, such as interfaith collaboration and the use of technology in learning, can be exploited. With a holistic and adaptive approach, Islamic religious education can strengthen Islamic identity, improve teacher quality, utilize technology, involve parents and the community, and realize comprehensive learning. This will help Islamic religious education become an important instrument in shaping student character, building interfaith harmony, and facing various challenges in modern life.Keyword : Islamic Religious Education; Multiculturalism; Secularism; Opportunities and Challenges